2009
DOI: 10.1016/j.ejpain.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pain induced by a single simulated office‐work session: Time course and association with muscle blood flux and muscle activity

Abstract: The present study aimed to assess the development of pain during computer work with high precision demand and time pressure, and the association between pain and muscle blood fluxes and muscle activity. Twenty-eight healthy subjects (range 22-44 years) performed a 90-min standardized task of correcting a text on a word-processor. Monetary reward was given according to productivity in order to induce time pressure. Pain intensity, general tension, and eye strain were reported on visual analogue scales before, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 55 publications
3
27
0
Order By: Relevance
“…In accordance with our results, they also found that patients in the dry needling group required a lower mean number of treatment sessions than patients in the stretching group. 7,10,13,14 Ma et al 41 also found that DDN together with stretching was more effective than self-stretching alone in MPS treatment. Nevertheless, they gave no indication of the number of treatments applied to each patient, or about what they did when the participant scored 0 in the VAS scale.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In accordance with our results, they also found that patients in the dry needling group required a lower mean number of treatment sessions than patients in the stretching group. 7,10,13,14 Ma et al 41 also found that DDN together with stretching was more effective than self-stretching alone in MPS treatment. Nevertheless, they gave no indication of the number of treatments applied to each patient, or about what they did when the participant scored 0 in the VAS scale.…”
Section: Discussionmentioning
confidence: 98%
“…Chronic overload of muscles, such as sustained contraction, as in computer work, or inadequate rest, has been widely reported by different authors as a cause of myalgia. [6][7][8]13 Some authors report the existence of a continuous activity of specific motor units in the trapezius during low-level muscle contraction, such as in computer use. 6,7,13 Kostopoulos and Rizopoulos 4 state that active MTrPs in the trapezius muscle are frequently found in patients with mechanical neck pain.…”
Section: 6-8mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperalgesia and discomfort occur frequently in seated workers 9) . Strøm et al suggested that the disturbance of vasodilatation in the upper trapezius region could decrease the pressurepain threshold associated with computer work 9,10) . This changed blood flux does not return to resting values even after work 10) .…”
Section: Display Terminalmentioning
confidence: 99%
“…Strøm et al suggested that the disturbance of vasodilatation in the upper trapezius region could decrease the pressurepain threshold associated with computer work 9,10) . This changed blood flux does not return to resting values even after work 10) . Hägg (1991) suggested that a degenerative process of type-1a muscle fibers is caused by fiber overuse, which induces pain in the upper trapezius region.…”
Section: Display Terminalmentioning
confidence: 99%